Effect of composition and heat treatment on the mechanical properties of Fe Mn Al steels (Fracture and Structural Integrity, 2022)
Starting from the research aimed at the development of substitute alloys for stainless steels, with the aim of replacing strategic metals such as chromium and nickel with the more available manganese, FeMnAlC alloys have been studied and developed for several years. These alloys exhibit an attractive strength/ductility combination, low density, and some of them show good oxidation behaviour at high temperatures. After a preliminary study, in this paper the effect of a solubilization treatment followed by aging in the temperature range 550 - 750 °C has been evaluated. The results of the investigation revealed that the steel characterized by the higher amount of Mn and Al shows, after heat treatment, the formation of phases that make the alloy very brittle. Considering the obtained results, it is evident that optimizing the alloy chemical composition is of paramount importance to guarantee a high fracture toughness if the steel works for limited time intervals at high temperature.
Keywords: Aging treatment; FeMnAl steels; Low density steels; Mechanical properties